The strain manipulation of nickel and permalloy spin valves - Al-Qayoudhi, Mohammed Salim (2020)
In spintronics devices, the manipulation of magnetisation in magnetic films and spin valves can play a crucial role in the development of novel technologies. The usage of strain-induced anisotropy utilised in spintronics devices can devise new methods for low-power storage and logic devices. One of these methods is using a multiferroic device to introduce strain throughout the magnetic materials. In this study, strain induced in ferromagnetic layers is accomplished by using a hybrid structure of piezoelectric transducer/ magnetic multi or single layers. The main aim of this thesis is to study the strain effect on the magnetisation and magnetic reversal of spin valves consisting of permalloy and nickel layers (with different magnetostriction values and sign) through the strain-induced magnetoelastic coupling.